Divine Reality and the Principle of Sufficient Reason: A Philosophical Analysis - Peter Ottuh; Onos Idjakpo (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2022)
The cosmological postulation that there cannot be an “effect” without a “cause” is the underlying predicate of the Principle of Sufficient Reason (PSR). PSR states that everything must have a sufficient reason, cause, or foundation. Some theologians consider the above notions to be fideism, preferring to think that God's knowledge is founded on human reason, whereas “intelligent design” is a two-tiered argument that uses design to show the existence of a “Divine Realty” (God). Reality is subjective and is built indirectly depending on human perspective. The paper, therefore, aimed to philosophically analyze the Principle of Sufficient Reason to explain the notion of a divine reality. This analytical philosophical research employs the descriptive and conceptual analysis approaches and reveals that PSR, like other concepts, is not only improbable, but is also contradictory to divine knowledge. It concludes that although PSR uses contradictory terms such as “necessity” and “contingency” and fails to provide adequate justification for the existence of a divine reality, it could be justified that a “Divine Reality” (God or necessary being) must have a “sufficient reason” to exist.